Dimensional stability of heat-activated acrylic resin at different time intervals by different flask cooling methods (Mustansiria Dental Journal, 2018)
This study was design to investigate the dimensional stability of heat-activated acrylic resin with different methods of flask cooling (15 minutes rapid cooling, one hour bench cooling, four hours delayed deflasking, and 24 hours delayed deflasking) at different time intervals (immediately, two days, seven days, 30 days) after deflasking.Heat-activated acrylic resin was used to prepare acrylic samples. Then, measurement of the distances where achieved between the centers of selected marks in the acrylic samples. They were measured at different time intervals for different methods of flask cooling.The results showed that the group samples of the four hours and 24 hours of delayed deflasking was insignificantly different from the control and followed by the group of one hour bench cooling. The quenched group was significantly different from the control group.The heat-activated acrylic resin should be kept in the flask for four hours or more after processing to achieve more accurate dentures.